Azaacenodibenzosuberones - Brosius, Victor; Müller, Matthias; Borstelmann, Jan; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (The journal of organic chemistry, 2020)
A series of dibenzosuberone-fused N-heteroacenes was obtained by the condensation of dibenzosuberonetriketone with a series of substituted diamino- and tetramino-arenes. The electron-deficient triketone reacts at room temperature and furnishes the pyrazine or bis-pyrazine-containing condensation products in good to excellent yield. The targets all display negative curvature according to single crystal structures.